"La Morale de Madame Dulska" – o francuskojęzycznej edycji dramatu Gabrieli Zapolskiej - Karwowska, Marzena (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2014)
The article presents the bilingual French-Polish publication, entitled La Morale de Madame Dulska. Moralność Pani Dulskiej (2011). Editors of the volume (Danuta Knysz-Tomaszewska, Grzegorz Bąbiak and Cécile Bocianowski) invited representatives of various universities to join the project, among them: Paris III Sorbonne (Elżbieta Koślacz-Virol), Paris IV Sorbonne (Danièle Chauvin) and University of Warsaw (Tomasz Wójcik). The play was translated by: Krzysztof Jeżewski – translator of Polish poetry into the French, also Elżbieta Koślacz-Virol, author of the book on Gabriela Zapolska published in France. La Morale de Madame Dulska was based on the translation by Paul Cazin (1881-1963).The French-Polish publishing initiative has been based on a copy of Paul Cazin’s manuscript donated by his widow, Juliette Monfet, in the late 1970s.